Island dreams. - Ross, P.E.
He writes code for the world's biggest telescope while cavorting in the Canaries. AstronomyÃ?Â¿s golden age, most astronomers will tell you, is right now. Four centuries after Galileo pointed his telescope skyward, that primordial instrument's fabulously complicated descendants are giving researchers stunning insights into black holes, the birth of galaxies, even the nature of physics itself. The whole enterprise depends on observatories that cost as much as atom smashers--and need about the same amount of automation.